Gamification: a key determinant of massive open online course (MOOC) success - Aparicio, Manuela (2019)
Aparicio, M., Oliveira, T., Bação, F., & Painho, M. (2019). Gamification: a key determinant of massive open online course (MOOC) success. Information and Management, 56(1), 39-54. [advanced online publication on 20 june 2018]. DOI: 10.1016/j.im.2018.06.003 ---%ABS3%